Expression and Regulation of Retinoic Acid Receptor Responders in the Human Placenta - Hübner, Hanna; Rascher, Wolfgang; Strick, Reiner; Kehl, Sven; Heindl, Felix; Wachter, David; Beckmann, Matthias; Fahlbusch, Fabian B.; Rübner, Matthias; Hartner, Andrea (Reproductive Sciences, 2017)
INTRODUCTION: Retinoic acid (RA) signaling through its receptors (RARA, RARB, RARG, and the retinoic X receptor RXRA) is essential for healthy placental and fetal development. An important group of genes regulated by RA are the RA receptor responders (RARRES1, 2, and 3). We set out to analyze their expression and regulation in healthy and pathologically altered placentas of preeclampsia (PE) and intrauterine growth restriction (IUGR) as well as in trophoblast cell lines. METHODS: We performed immunohistochemical staining on placental sections and analyzed gene expression by real-time polymerase chain reaction. Additionally, we performed cell culture experiments and stimulated Swan71 and Jeg-3 cells with different RA derivates and 2'-deoxy-5-azacytidine (AZA) to induce DNA demethylation. RESULTS: RARRES1, 2, and 3 and RARA, RARB, RARG, and RXRA are expressed in the extravillous part of the placenta. RARRES1, RARA, RARG, and RXRA were additionally detected in villous cytotrophoblasts. RARRES gene expression was induced via activation of RARA, RARB, and RARG in trophoblast cells. RARRES1 was overexpressed in villous trophoblasts and the syncytiotrophoblast from PE placentas, but not in IUGR without PE. Promoter methylation was detectable for RARRES1 and RARB based on their sensitivity toward AZA treatment of trophoblast cell lines. DISCUSSION: RARRES1, 2 and 3 are expressed in the functional compartments of the human placenta and can be regulated by RA. We hypothesize that the epigenetic suppression of trophoblast RARRES1 and RARB expression and the upregulation of RARRES1 in PE trophoblast cells suggest an involvement of environmental factors (eg, maternal vitamin A intake) in the pathogenesis of this pregnancy complication.
EVALuna2:34222